Building university schools in teacher education programmes guidelines and suggestions - Lazarová, Bohumíra; Pol, Milan; Moškvan, Vladimír; Gerholz, Karl-Heinz; Neubauer, Jörg; Reinke, Hannes; Wagner, Anne; Marko, Nils; Seitle, Johannes; Wilbers, Karl (Masaryk University Press, 2021)
Intro -- Content -- Introduction -- 1. Organization of student teachers' internship -- 1.1 Selection of the university schools -- 1.2 Partnership, collaboration and agreements -- 1.2.1 Formal agreements on the organization of practices - information and methods -- 1.2.2 Written contracts - legal documents -- 1.3 Resources -- 1.3.1 Human resources -- 1.3.2 Finances -- 1.3.3 Literature and education -- 1.3.4 Time -- 1.3.5 Space -- 1.3.6 Online support -- In sum… -- 2. Internship activities -- 2.1 Enrolling students for internship and their socialization in school -- 2.2 Observation in and beyond the classroom -- 2.3 Tandem teaching -- 2.4 Lesson preparation and individual teaching -- 2.5 Individual and group reflection with school-based teacher educator(s) -- 2.6 Students as researchers -- 2.7 Evaluation and documentation of the internship by the student -- 2.8 Documentation of internships by the mentor -- In sum… -- 3. Requirements for school-based teacher educators -- 3.1 Selection of the school-based teacher educators -- 3.2 School-based teacher educator's competences -- 3.3 School-based teacher educator's education -- 3.4 Supervision and further support for school-based teacher educators -- In sum… -- Conclusion -- References -- Appendices -- Appendix 1 Resolution and Faculty school status -- Appendix 2 Preparation of rules and measures: Analysis of concerns, temptations and tendencies -- Appendix 3 Observation sheet class leadership - field of action class "manage, organize, lead, and represent" -- Appendix 4 Observation sheet -- Appendix 5 Effective feedback -- Appendix 6 Reflection concept in Bamberg
Keywords: Schulpraktikum; Lehramtsstudium